2016
DOI: 10.3390/nu8070392
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Absorbing Modified Starch before and during Prolonged Cycling Increases Fat Oxidation and Gastrointestinal Distress without Changing Performance

Abstract: While prior research reported altered fuel utilization stemming from pre-exercise modified starch ingestion, the practical value of this starch for endurance athletes who consume carbohydrates both before and during exercise is yet to be examined. The purpose of this study was to determine the effects of ingesting a hydrothermally-modified starch supplement (HMS) before and during cycling on performance, metabolism, and gastrointestinal comfort. In a crossover design, 10 male cyclists underwent three nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
15
2
Order By: Relevance
“…Probabilistic magnitude-based inferences and 90% confidence intervals (CI) were used to assess the effect of pre-sleep WP and CP on the metabolic variables and RE volume, when compared to the PLA using the methods detailed by Batterham and Hopkins [ 26 ]. Several performance and sports nutrition studies [ 7 , 27 , 28 ] have used this approach as an alternative to traditional null hypothesis testing. A published spreadsheet was used to assess the likelihood of a true treatment effect, based on the smallest meaningful threshold [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Probabilistic magnitude-based inferences and 90% confidence intervals (CI) were used to assess the effect of pre-sleep WP and CP on the metabolic variables and RE volume, when compared to the PLA using the methods detailed by Batterham and Hopkins [ 26 ]. Several performance and sports nutrition studies [ 7 , 27 , 28 ] have used this approach as an alternative to traditional null hypothesis testing. A published spreadsheet was used to assess the likelihood of a true treatment effect, based on the smallest meaningful threshold [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, nutrient ingestion prior to and during exercise may lead to GID. Baur and colleagues (2016) reported that GID increased after the consumption of the same hydrothermally modified starch (HMS) LGI supplement that our current study used [ 15 ]. Baur et al (2016) compared the HMS to an HGI CHO supplement when ingested prior to, and during, prolonged cycling in ten trained male cyclists and triathletes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baur and colleagues (2016) reported that GID increased after the consumption of the same hydrothermally modified starch (HMS) LGI supplement that our current study used [ 15 ]. Baur et al (2016) compared the HMS to an HGI CHO supplement when ingested prior to, and during, prolonged cycling in ten trained male cyclists and triathletes [ 15 ]. It was reported that there were likely large correlations between mean sprint nausea ( r = −0.51) and total GID ( r = −0.53) and exercise trial, showing that GID contributed to reduced cycling performance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations